2017
DOI: 10.1038/srep45043
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus hemagglutinin and neuraminidase act as novel motile machinery

Abstract: Influenza A virus (IAV) membrane proteins hemagglutinin (HA) and neuraminidase (NA) are determinants of virus infectivity, transmissibility, pathogenicity, host specificity, and major antigenicity. HA binds to a virus receptor, a sialoglycoprotein or sialoglycolipid, on the host cell and mediates virus attachment to the cell surface. The hydrolytic enzyme NA cleaves sialic acid from viral receptors and accelerates the release of progeny virus from host cells. In this study, we identified a novel function of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(158 citation statements)
references
References 41 publications
10
146
1
1
Order By: Relevance
“…This peak decreases with added NA inhibitor and is therefore ascribed to receptor cleaving by NA. Block et al claim that the lateral diffusion of the glycolipids to which inuenza binds remains signicantly faster than the NA-dependent motility that was reported by Sakai et al 15,17 It is interesting to note the differences in setup and observed mobility between these four publications. Both Block et al and Sakai et al used an egg-adapted inuenza strain with HA and NA from the IAV strain Aichi/2/68 (H3N2).…”
Section: Motility Of Influenza Virusmentioning
confidence: 87%
See 4 more Smart Citations
“…This peak decreases with added NA inhibitor and is therefore ascribed to receptor cleaving by NA. Block et al claim that the lateral diffusion of the glycolipids to which inuenza binds remains signicantly faster than the NA-dependent motility that was reported by Sakai et al 15,17 It is interesting to note the differences in setup and observed mobility between these four publications. Both Block et al and Sakai et al used an egg-adapted inuenza strain with HA and NA from the IAV strain Aichi/2/68 (H3N2).…”
Section: Motility Of Influenza Virusmentioning
confidence: 87%
“…[50][51][52][53] It is likely that the organization of HA and NA has an inuence on the way their functions cooperate. Motility of inuenza was rst reported by Sakai et al 15 They tracked the motion of inuenza viruses over fetuin-modied glass with total internal reection uorescence microscopy (TIRF). When adding an NA inhibitor, the movement of the viruses was completely blocked.…”
Section: Motility Of Influenza Virusmentioning
confidence: 92%
See 3 more Smart Citations